Repairing, Maintenance and Cleaning Services (RMCC) - a conceptual enhanced business model - Habib, Nasratullah; Abdullahi, Zakaria Yassin; Ahmad Dahlan, Abdul Rahman (IEEE, 2018)
The purpose of this paper is to present services to people which might help them overcome their daily problems with cleaning, repairing, and maintaining of their houses, schools, universities and other living places. In addition, this is also helping people to have time for their other daily routines. Nowadays, many people are struggling with health problems; the reason is not to have clean and tidy living places due to the busy life. Therefore, this paper is proposing a conceptual biz model to overcome the pain and to find gain, utilizing Business Model Canvas (BMC), UPD, Literature Reviews, benchmarking, 4 Lenses of Innovation, and Value Proposition Design (VPD).